IMPLEMENTASI CYBER PUBLIC RELATIONS DALAM PEMBENTUKAN CITRA KEPOLISIAN RESOR KOTA (POLRESTA) SAMARINDA - Suci Ashari; Annisa Wahyuni Arsyad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The new era of rapid development of information technology today not only affects some aspects, but also activities carried out by PR (Public Relations) practitioners. This indirectly requires PR practitioners to face changes, namely the transition from the conventional era to the digital era. Conventional to digital PR activities are also known as Cyber Public Relations (CPR). One of the challenges of PR in the digital world is managing negative opinions from the public that can affect the positive image built by the organization. Currently, police agencies are one of the state institutions that are vulnerable to negative public opinion and are often threatened by their reputation in the eyes of the public. Therefore, this research aims to examine the implementation of Cyber Public Relations of Samarinda Police in shaping a positive image in the eyes of the community and what obstacles are experienced to form a positive image. In this research, the theory used is the Excellence of Public Relations theory. To reveal these issues thoroughly and in depth, this research uses a qualitative method with a descriptive approach to explain the situation and conditions of Cyber Public Relations activities of Samarinda Police. The results of this study indicate that the implementation of Cyber Public Relations by the Public Relations of Samarinda Police has not been carried out comprehensively. CPR activities of Samarinda Police only reach the level of press agentcy and public information, Public Relations also has not involved the community in CPR activities to improve their image. Some of the obstacles experienced by Samarinda Police Public Relations are related to the lack of human resources and interaction from the public in the media they manage.